Corneal Astigmatism Measurements Comparison among Ray-Tracing Aberrometry, Partial Coherence Interferometry, and Scheimpflug Imaging System - Yaqin Zhang; Jing Dong; Suhua Zhang; Bin Sun; Xiaoliang Wang; Maolong Tang; Xiaogang Wang (Journal of Ophthalmology)
Purpose. To investigate interdevice agreement among corneal topography/ray-tracing aberrometry (iTrace), partial coherence interferometry (IOLMaster), and Scheimpflug imaging (Pentacam) for the measurement of corneal astigmatism. Methods. The analysis included 90 eyes of 90 subjects without ocular disease. The main outcome measures were corneal cylinder power and axis of astigmatism. All corneal astigmatism measurements were converted to two perpendicular components by using vector analysis. Interdevice agreement was assessed using Bland–Altman analysis, paired sample t-test, and one-way analysis of variance. Results. No significant interdevice difference existed in the astigmatism magnitude, cardinal component, and oblique component (all P>0.05). On comparing iTrace wavefront and simulated keratometry (SimK) astigmatism, significant differences were observed in the astigmatism magnitude and oblique component (both P<0.01), but not in the cardinal component (P=0.687). On comparing Pentacam pupil 3 mm and corneal vertex 3 mm axial astigmatism, significant difference was observed in the astigmatism magnitude (P<0.001), but not in the cardinal and oblique components (both P>0.05). Conclusions. The iTrace, IOLMaster, and Pentacam devices could be used interchangeably for corneal astigmatism measurement. However, the measurement difference in iTrace wavefront and SimK astigmatism and Pentacam pupil 3 mm and vertex 3 mm axial astigmatism should be considered in clinic practice.